Age differences in the severity, impact and relative importance of dynamic risk factors for recidivism. (May 2017) - Spruit, Anouk; van der Put, Claudia; Gubbels, Jeanne; Bindels, Anner
Abstract: Research in adolescent populations has shown that the severity, impact, and relative importance of dynamic risk factors for recidivism changes over the course of adolescence. This study examined whether there were age differences in the severity, impact, and relative importance of dynamic risk factors for recidivism in an adult offender population. The sample consisted of 8665 Dutch offenders and was divided into four age groups: 18–25 years old, 26–30 years old, 31–40 years old, and 41 + years old. The results showed that the severity and impact of dynamic risk factors varied across the age groups. An increase of the impact of dynamic risk factors was found over the course of adulthood, indicating that dynamic risk factors had a larger predictive power for recidivism in the older age groups. The relative importance of the risk factors also varied across age. In late adolescence, recidivism was most strongly predicted by problems in the education, alcohol use, and peer domains, whereas in adulthood, problems with drugs and alcohol were the most important predictors of recidivism. Results emphasize the importance of directing offender treatment at high risk offenders, and the focus on age specific criminogenic needs to maximize the effect of treatment. Highlights: The severity, impact, and relative importance of risk factors for recidivism were examined. In middle adulthood, the severity of dynamic risk factors for recidivism peaked. Over the course of adulthood, recidivism was increasingly predicted by the dynamic risk factors. The relative importance of risk factors differed across age groups. Risk factors from the individual domain gained importance over the course of adulthood.